Social, Demographic and Labour Market Related Determinants of Health in the Adult European Population - Agnes Rozsa Santha (Finnish Yearbook of Population Research, 2017)
This paper identifies the social, demographic and labour market related determinants of the state of health and assesses the magnitude of their impact within the European adult population. The research is based on a statistical analysis on the data of the European Social Survey (ESS), round 7, 2014/2015. Subjective socioeconomic situation and partnership status are being identified as the most influential social determinants of health. Results also illuminate how work-life-balance determines health. People suffering from work-life-imbalance are more likely to become ill than those with more free time and flexible working hours.